2019
DOI: 10.1021/acs.analchem.9b04803
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Quantitation of Supramolecular Excipient@Drug Complexation: A General Assay Strategy Based on Competitive Host Binding with Surface-Immobilized Redox Guest

Abstract: The macrocyclic cucurbit [7]uril (CB[7]) host has exhibited great application potential as a pharmaceutical excipient due to its versatile abilities to modulate the chemical/physical properties of drug molecules (guests) and to control their in vivo delivery and release (upon complexation). The formation of stable CB[7]@drug complexes is the prerequisite for these promising applications; we report herein a general assay strategy to quantitate the complexation based on competitive binding with surface-immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…However, most guest compounds of CB [7] are not redox-active, so that their host− guest binding affinities have to be studied by using advanced spectroscopic techniques (e.g., NMR, UV/vis spectroscopy) or isothermal titration calorimetry (ITC). 42 We have shown that cyclic voltammetry (CV) can be successfully employed to quantitate the host−guest binding between CB [7] and a number of other guests based on thier competitive binding with redox-active CB [7]@Fc complexes preformed on FcC11S−/C8S−Au, 42 as illustrated in Figure 6A. Specifically, from the molar ratio of free and CB [7]-bound Fc terminal groups at competitive binding equilibrium and the formation constant (K 1 ) of interfacial CB [7]@Fc complexation, the equilibrium concentration of free CB [7] (c CB [7] ) can be obtained from eq 2; the equilibrium concentrations of nonredox-active guest (c guest ) and its host−guest complex with CB [7] (c CB [7]@guest ) can be subsequently determined as well.…”
Section: Binding Of Cb[7] Host On Fc-alkanethiolate Sams On Gold: Fro...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, most guest compounds of CB [7] are not redox-active, so that their host− guest binding affinities have to be studied by using advanced spectroscopic techniques (e.g., NMR, UV/vis spectroscopy) or isothermal titration calorimetry (ITC). 42 We have shown that cyclic voltammetry (CV) can be successfully employed to quantitate the host−guest binding between CB [7] and a number of other guests based on thier competitive binding with redox-active CB [7]@Fc complexes preformed on FcC11S−/C8S−Au, 42 as illustrated in Figure 6A. Specifically, from the molar ratio of free and CB [7]-bound Fc terminal groups at competitive binding equilibrium and the formation constant (K 1 ) of interfacial CB [7]@Fc complexation, the equilibrium concentration of free CB [7] (c CB [7] ) can be obtained from eq 2; the equilibrium concentrations of nonredox-active guest (c guest ) and its host−guest complex with CB [7] (c CB [7]@guest ) can be subsequently determined as well.…”
Section: Binding Of Cb[7] Host On Fc-alkanethiolate Sams On Gold: Fro...mentioning
confidence: 99%
“…As described above, Fc and other redox-active guests allow for the use of a simple but sensitive electrochemical method to study their host–guest binding with CB[7]. However, most guest compounds of CB[7] are not redox-active, so that their host–guest binding affinities have to be studied by using advanced spectroscopic techniques (e.g., NMR, UV/vis spectroscopy) or isothermal titration calorimetry (ITC) . We have shown that cyclic voltammetry (CV) can be successfully employed to quantitate the host–guest binding between CB[7] and a number of other guests based on thier competitive binding with redox-active CB[7]@Fc complexes preformed on FcC11S–/C8S–Au, as illustrated in Figure A.…”
Section: Binding Of Cb[7] Host On Fc-alkanethiolate Sams On Gold: Fro...mentioning
confidence: 99%
“…In recent years, AuNCs have been used in the ECL biosensing field due to their uniform and controllable size, biocompatibility, and stable optical properties. Despite swift progress in the ECL application of AuNCs, it still turns out to be rather challenging for realizing simple synthesis, excellent stability, and high ECL efficiency, which is critical for improving their performance in the ECL biosensing application. It has been demonstrated that passivation and reduction of the surface energy can enhance the stability and improve the ECL performance of AuNCs. In this respect, cucurbit[7]­uril (CB[7]) assisted supramolecular self-assembly is probably a desirable and straightforward strategy for enhancing the ECL intensity and stability of AuNCs. CB[7] is a highly rigid, pumpkin-shaped macrocyclic supermolecule comprising seven glycoluril units bridged by methylene groups. Under the impacts of various non-covalent interactions such as hydrogen bond effect, hydrophobic effects, the polar and hydrophobic inner cavity, ion-dipole, and two portals with the negative charge, CB[7] exhibits binding solid force with the specific guest in aqueous solution, forming a stable host–guest complex. The outstanding rigidity, water solubility, and supramolecular recognition ability allow CB[7] to act as “intelligent molecular shackles” to recognize and limit the vibrations and interactions of ligands on the surface of Au NCs. This supramolecular recognition approach effectively suppresses the non-radiative rate and reduces the agglomeration of Au NCs in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…54 As an alternative stimulus-responsive supramolecular strategy, guest competition is a straightforward strategy that is used in drug delivery and sensing applications. 55 Competitive guests with a higher binding affinity may give priority to the formation of host-guest complexes and even squeeze other guests out of the cavity of supramolecular macrocycles. On the basis of the light stimulus-responsive system, competitive host-guest recognition was also confirmed.…”
mentioning
confidence: 99%
“…28 Before MV2 addition, the solution of AZO (0.1 mM) and CB [8] (0.2 mM) could produce a signal with the probability of 11.5%, which is reasonable for SMFS measurements. [55][56][57] When the concentration of MV2 reached 0.2 mM, the probability drifted to 9.0% (78.2% of the initial probability). After more MV2 addition, the probability continuously drifted to 6.2% (53.9% of the initial probability, [MV2] = 1 mM) and 3.6% (31.3% of the initial probability, [MV2] = 5 mM).…”
mentioning
confidence: 99%